Parenting Practices at 24 to 47 Months and IQ at Age 8: Effect-Measure Modification by Infant Temperament. - Shiau Yun Chong; Catherine R Chittleborough; Tess Gregory; Murthy N Mittinty; John W Lynch; Lisa G Smithers (PLoS ONE)
Cognitive development might be influenced by parenting practices and child temperament. We examined whether the associations between parental warmth, control and intelligence quotient (IQ) may be heightened among children in difficult temperament. Participants were from the Avon Longitudinal Study of Parents and Children (n = 7,044). Temperament at 6 months was measured using the Revised Infant Temperament Questionnaire and classified into 'easy' and 'difficult'. Parental warmth and control was measured at 24 to 47 months and both were classified into 2 groups using latent class analyses. IQ was measured at 8 years using the Wechsler Intelligence Scale for Children and dichotomized (<85 and ≥85) for analyzing effect-measure modification by temperament. Linear regression adjusted for multiple confounders and temperament showed lower parental warmth was weakly associated with lower IQ score [β = -0.52 (95% CI 1.26, 0.21)], and higher parental control was associated with lower IQ score [β = -2.21 (-2.95, -1.48)]. Stratification by temperament showed no increased risk of having low IQ in temperamentally difficult children [risk ratio (RR) = 0.97 95% CI 0.65, 1.45)] but an increased risk among temperamentally easy children (RR = 1.12 95% CI 0.95, 1.32) when parental warmth was low. There was also no increased risk of having low IQ in temperamentally difficult children (RR = 1.02 95% CI 0.69, 1.53) but there was an increased risk among temperamentally easy children (RR = 1.30 95% CI 1.11, 1.53) when parental control was high. For both parental warmth and control, there was some evidence of negative effect-measure modification by temperament on the risk-difference scale and the risk-ratio scale. It may be more appropriate to provide parenting interventions as a universal program rather than targeting children with difficult temperament.